Design and Modeling of Mechanical Systems - IV : Proceedings of the 8th Conference on Design and Modeling of Mechanical Systems, CMSM'2019, March 18–20, Hammamet, Tunisia /: Proceedings of the 8th Conference on Design and Modeling of Mechanical Systems, CMSM'2019, March 18–20, Hammamet, Tunisia. (2020) - Unknown
No abstract available